Pendampingan Partisipatif Guru dalam Menghidupkan Karawitan sebagai Warisan Budaya Lokal di Desa Ngastemi - Ahmad Aly Syukron Aziz Al Mubarok; A. Fandi Bastian; Imam Wahyudi; Alif’uan Nur Reza; Dewi Syafitri; Sri Wahyuni (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2026)
This community empowerment program aims to strengthen teachers’ cultural competence through participatory mentoring in karawitan activities in Ngastemi Village, Bangsal District, Mojokerto. The program employed Participatory Action Research (PAR) to actively involve teachers as subjects of empowerment. Activities included socialization, basic gamelan training, guided practice, and reflective evaluation. The results indicate an increase in teachers’ skills in playing gamelan, growing awareness of local cultural preservation, and the formation of routine karawitan practice. The program demonstrates that participatory mentoring is effective in revitalizing local cultural heritage through teacher empowerment and has potential for replication.